2019
DOI: 10.1017/jfm.2019.327
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of local entrainment and detrainment in a turbulent jet

Abstract: In this paper we investigate the continuous, local exchange of fluid elements as they are entrained and detrained across the turbulent/non-turbulent interface (TNTI) in a high Reynolds number axisymmetric jet. To elucidate characteristic kinematic features of local entrainment and detrainment processes, simultaneous high-speed particle image velocimetry and planar laser-induced fluorescence measurements were undertaken. Using an interface-tracking technique, we evaluate and analyse the conditional dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 43 publications
13
49
0
Order By: Relevance
“…A more recent work by Mistry et al. (2019), which discusses the existence of instantaneous detrainment zones in a turbulent jet, further supports our observations on the detrainment near the VLCSs. Here, the authors show that, similarly to our findings, high detrainment is observed when the fluid moves tangentially to the interface on both sides of the TNTI.…”
Section: Discussion and Summarysupporting
confidence: 91%
See 1 more Smart Citation
“…A more recent work by Mistry et al. (2019), which discusses the existence of instantaneous detrainment zones in a turbulent jet, further supports our observations on the detrainment near the VLCSs. Here, the authors show that, similarly to our findings, high detrainment is observed when the fluid moves tangentially to the interface on both sides of the TNTI.…”
Section: Discussion and Summarysupporting
confidence: 91%
“…2014; Krug et al. 2017 a ), unconditioned averages of are negative (entrainment), but instantaneous positive (detrainment) values can be observed (Mistry, Philip & Dawson 2019). To interpret the latter, one can take into account the local entrainment velocity decomposition based on the turbulent enstrophy equation introduced by Holzner & Lüthi (2011).…”
Section: Resultsmentioning
confidence: 99%
“…Hypothesizing a constant entrainment velocity over the TNTI, he concluded that, on average, the curvature/propagation effect creates TNTI area along the bulges and destroys it in the valleys of the TNTI. While this is an important theoretical finding, the local entrainment velocity is known to vary significantly along the TNTI (Holzner & Lüthi 2011;Wolf et al 2012;Watanabe et al 2014), with a predominance of negative values implying entrainment that alternate with sporadic positive values representing detrainment zones (Wolf et al 2012; Krug et al 2017a;Mistry, Philip & Dawson 2019). In this work, we evaluate locally the stretching and the curvature/propagation terms on the TNTI in order to assess their role in the time evolution of surface area of the TNTI.…”
Section: Introductionmentioning
confidence: 98%
“…Related findings were presented by Lee, Sung & Zaki (2017), who used a conditional analysis to show that the surface area of the TNTI increases in the vicinity of large-scale motions of a turbulent boundary layer. More recently, vortical structures near the TNTI have been shown to influence both the intensity of the local entrainment velocity and the mean curvature of the TNTI (Mistry et al 2019;Neamtu-Halic et al 2019). This suggests that vortical structures may impact the evolution of the TNTI area.…”
Section: Introductionmentioning
confidence: 99%
“…da Silva & Taveira 2010;Jahanbakhshi, Vaghefi & Madnia 2015) reveal the presence of a large vorticity structure (LVS) of the order of the Taylor microscale around the TNTI. These structures are found to play an important role in the entrainment of irrotational fluid (da Mistry et al 2019). The TNTI thickness is reported to be of the order of λ owing to the presence of such LVSs around it (da Silva & Taveira 2010).…”
mentioning
confidence: 99%